2020
DOI: 10.1002/cpdd.848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ABCB1, UGT1A1, and UGT1A9 Genetic Polymorphisms on the Pharmacokinetics of Sitafloxacin Granules in Healthy Subjects

Abstract: Sitafloxacin, a new fluoroquinolone, has strong antibacterial activity. We evaluated the effects of sitafloxacin granules in single-dose and multidose cohorts and the effects of ABCB1, UGT1A1, and UGT1A9 genetic polymorphisms on the pharmacokinetics (PK) of sitafloxacin in healthy subjects. The single-dose study included 3 fasted cohorts receiving 50, 100, and 200 mg of sitafloxacin granules and 1 cohort receiving 50 mg of sitafloxacin granules with a high-fat meal. The multidose study included 1 cohort receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…SNPs in UGT1A9 rs2741049 and rs3832043 have a longer half-life (t 1/2 ) than those in subjects without the variant; this was thought to occur due to decreased metabolism and disposition of sitafloxacin. However, this study did not show significant changes in AUC in either the ABCB1 or UGT1A9 groups (Sun et al, 2021). Acyl glucuronidation of trovafloxacin has been studied in human liver microsomes and also in UGT isoform-expressing systems in human liver microsomes.…”
Section: Figurecontrasting
confidence: 54%
See 4 more Smart Citations
“…SNPs in UGT1A9 rs2741049 and rs3832043 have a longer half-life (t 1/2 ) than those in subjects without the variant; this was thought to occur due to decreased metabolism and disposition of sitafloxacin. However, this study did not show significant changes in AUC in either the ABCB1 or UGT1A9 groups (Sun et al, 2021). Acyl glucuronidation of trovafloxacin has been studied in human liver microsomes and also in UGT isoform-expressing systems in human liver microsomes.…”
Section: Figurecontrasting
confidence: 54%
“…Polymorphism of UGT1A1 , UGT1A9 , and ABCB1 also affects the pharmacokinetic profile in sitafloxacin and trovafloxacin ( Figure 1 ; Table 2 ). A study on sitafloxacin showed that there was an association of genetic polymorphism of the human drug transporter ABCB1 rs1045642 in subjects with heterozygous or homozygous genotype variants with a lower C max of sitafloxacin than that in subjects without variants ( p < 0.05) ( Sun et al, 2021 ). SNPs in UGT1A9 rs2741049 and rs3832043 have a longer half-life (t 1/2 ) than those in subjects without the variant; this was thought to occur due to decreased metabolism and disposition of sitafloxacin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations